Report from the Field: Multi-cultural Dialogue and Transformative Learning in Arts & Minds Programs at The Studio Museum in Harlem - Carolyn Halpin-Healy (Museum & Society, 2015)
This paper presents a report from the field of museum education programs for people with Alzheimer’s disease and related dementias (ADRD) and their caregivers. Research is beginning to document the impact of museums on the cognitive and emotional health of people with dementia (PWD) and those who care for them. At the Studio Museum in Harlem, Arts & Minds programs have created a dynamic learning environment for the very forgetful through dialogic interpretation of art and expressive art making. The stories recounted here reveal the powerful potential of multi-cultural dialogue in the museum space to create transformative learning experiences for participants and educators alike.